The Stereotype with Jazz Music from slavery Music to Elitist Music (1959-1988): Indonesian Jazz History - Aryo, Aryo Sanjaya (PERIODE: Jurnal Sejarah dan Pendidikan Sejarah, 2023)
Abstract: This study aims to describe the development of Jazz music in Indonesia and the existence of Jazz music in Indonesia from 1959 to 1988. The research method used is historical research method whose steps consist of gathering sources (heuristics), source criticism (verification), interpretation (interpretation), and writing (historiography). In the first stage the writer collects primary sources in the form of newspapers, magazines and historical actors, as well as secondary sources such as books and journals. After the data is collected, it is then verified externally and internally. Next, interpret the meaning of facts and the relationship between one fact and another. The author brings together the facts that have been interpreted. The final stage is thesis writing. This research yields information that historically Jazz music was banned in Indonesia during Soekarno's reign and was finally allowed to be developed again during Suharto's reign. 1959 marked the banning of Jazz music through the MANIFESPOL issued by Soekarno, even though in its history this period was the heyday of Jazz music in Indonesia. Then 1988 was the year Jak Jazz was formed as the largest international scale Indonesian Jazz music festival at that time. Jak Jazz indicates that Jazz music is being accepted again and is starting to spread its wings to the general public. It can be concluded that the history of jazz in Indonesia is very long and can be influenced by political policies so that in the end we can listen to the masterpieces of jazz musicians at that time today. Keyword: Jazz, MANIPOL, Indonesian Jazz History